Optimized video internet of things using elliptic curve cryptography based encryption and decryption. (July 2022) - Alhayani, Bilal S.A.; Hamid, Nagham; Almukhtar, Firas Husham; Alkawak, Omar A.; Mahajan, Hemant B.; Kwekha-Rashid, Ameer Sardar; İlhan, Haci; Marhoon, Haydar Abdulameer; Mohammed, Husam Jasim; Chaloob, Ibrahim Zeghaiton; Alkhayyat, Ahmed
Abstract: The adaptive Joint Photographic Experts Group 2000 (JPEG2000) image compression approach employing the wavelet image transform had proposed with the rise of the optimized Video Internet of Things (VIoT) using image transmission security using Elliptic Curve Cryptography (ECC) techniques. Compressive Sensing (CS) for periodic data transfers has shown to be an excellent option for Wireless Sensor Networks (WSNs) since CS-based sensor communications drastically reduce data transmissions and enhance energy efficiency. However, another issue that arises when utilizing the optimized VIoT with image transmission compression is data loss as a result of various security risks during transmission. The numerous cooperative communication strategies proved their feasibility in different ways. However, additional issues must be handled while handling image transmission in VIoT. For example, when preparing to transmit an image, you may expend a lot of energy. The main objective of this paper is to increase image quality while minimizing processing time and error rates. However, force aptitude is vital to the research problem for the Wireless Multimedia Sensor Network (WMSN), as high-dimensional digital images use greater processing capabilities of sensor nodes. The image in WMSN is transmitted through a large number of relays. The experimental findings demonstrate the effectiveness of the suggested paradigm.